Genetic and Pharmacologic Hydrogen Sulfide Therapy Attenuates Ischemia-Induced Heart Failure in Mice - Calvert, John W. (2010)
BACKGROUND: Hydrogen sulfide (H(2)S) is an endogenous signaling molecule with potent cytoprotective effects. The present study evaluated the therapeutic potential of H(2)S in murine models of heart failure. METHODS AND RESULTS: Heart failure was induced by subjecting mice either to permanent ligation of the left coronary artery for 4 weeks or to 60 minutes of left coronary artery occlusion followed by reperfusion for 4 weeks. Transgenic mice with cardiac-restricted overexpression of the H(2)S-generating enzyme cystathione γ-lyase (αMHC-CGL-Tg(+)) displayed a clear protection against left ventricular structural and functional impairment as assessed by echocardiography in response to ischemia-induced heart failure, as well as improved survival in response to permanent myocardial ischemia. Exogenous H(2)S therapy (Na(2)S; 100 μg/kg) administered at the time of reperfusion (intracardiac) and then daily (intravenous) for the first 7 days after myocardial ischemia also protected against the structural and functional deterioration of the left ventricle by attenuating oxidative stress and mitochondrial dysfunction. Additional experiments aimed at elucidating some of the protective mechanisms of H(2)S therapy found that 7 days of H(2)S therapy increased the phosphorylation of Akt and increased the nuclear localization of 2 transcription factors, nuclear respiratory factor 1 and nuclear factor-E2-related factor (Nrf2), that are involved in increasing the levels of endogenous antioxidants, attenuating apoptosis, and increasing mitochondrial biogenesis. CONCLUSIONS: The results of the present study suggest that either the administration of exogenous H(2)S or the modulation of endogenous H(2)S production may be of therapeutic benefit in the treatment of ischemia-induced heart failure.